2009
DOI: 10.1017/s1368980008003182
|View full text |Cite
|
Sign up to set email alerts
|

Fish intake and the risk of fatal prostate cancer: findings from a cohort study in Japan

Abstract: Objective: We investigated the relationship between the intake of fish and the risk of death from prostate cancer. Design: Data were derived from a prospective cohort study in Japan. Fish consumption obtained from a baseline questionnaire was classified into the two categories of 'low intake' and 'high intake'. The Cox proportional hazards model was used to estimate hazard ratios (HR) and 95 % confidence intervals. Subjects: Data for 5589 men aged 30-79 years were analysed. Results: A total of twenty-one prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 27 publications
(39 reference statements)
0
41
1
5
Order By: Relevance
“…Augustsson et al [33] reported on a large prospective cohort from the US Health Professionals Follow-Up Study and found that men who ate fish more than 3 times per week were approximately half as likely to develop metastatic cancer as those who ate fish less than twice per month. Three additional cohort studies reported significantly reduced rates of prostate can-cer-specific mortality in those men consuming larger quantities of fish [34,51,60] .…”
Section: Pufas and Risk Of Advanced Prostate Cancermentioning
confidence: 99%
“…Augustsson et al [33] reported on a large prospective cohort from the US Health Professionals Follow-Up Study and found that men who ate fish more than 3 times per week were approximately half as likely to develop metastatic cancer as those who ate fish less than twice per month. Three additional cohort studies reported significantly reduced rates of prostate can-cer-specific mortality in those men consuming larger quantities of fish [34,51,60] .…”
Section: Pufas and Risk Of Advanced Prostate Cancermentioning
confidence: 99%
“…Mounting evidence has linked the dietary consumption of Ω-3 PUFAs with the prevention or attenuation of several types of cancer, including breast (27), endometrial (28) and prostate (6)(7)(8)(9) cancer. In the present study, VCaP cells were exposed to either AA or EPA, and it was demonstrated that while EPA inhibited prostate cancer cell proliferation in a dose-dependent manner, AA stimulated cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, a high incidence of prostate cancer is associated with excessive consumption of Ω-6 polyunsaturated fatty acids (PUFAs), commonly found in red and organ meats, refined vegetable oils and cooked processed meat (3)(4)(5). Conversely, evidence suggests that an Ω-3 PUFA-rich diet is inversely associated with prostate cancer development (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…W badaniu wykazano, że u mężczyzn spożywa-jących najwięcej ryb (powyżej 130 g/d) ryzyko występowania raka stercza było o 55% mniejsze niż u mężczyzn spożywających ryby w ilości mniejszej niż 47 g/d. W badaniu Pham et al [14] zaobserwowano, że duże spożycie ryb było odwrotnie skorelowane z ryzykiem śmierci spowodowanym rakiem gruczołu krokowego. W badaniu tym wyodrębniono 2 grupy mężczyzn na podstawie ilości spożywanych ryb.…”
Section: Kwasy Tłuszczoweunclassified